A new recombinant MS-superoxide dismutase alleviates 5-ﬂuorouracil-induced intestinal mucositis in mice - Yan Xiao-xia; Li Hai-long; Zhang Yi-ting; Wu Shou-yan; Lu Heng-lei; Yu Xiao-lu; Meng Fan-guo; Sun Jian-hua; Gong Li-kun (Acta Pharmacologica Sinica; Vol 41, No 3 (March 2020): Acta Pharmacologica Sinica, 2020)
Intestinal mucositis is a common side effect of anticancer regimens that exerts a negative impact on chemotherapy. Superoxide dismutase (SOD) is a potential therapy for mucositis but efficient product is not available because the enzyme is degraded following oral administration or induces an immune reaction after intravascular infusion. Multi-modified Stable Anti-Oxidant Enzymes® (MS-AOE®) is a new recombinant SOD with better resistance to pepsin and trypsin. We referred it as MS-SOD to distinguish from other SODs. In this study we investigated its potential to alleviate 5-FU-induced intestinal injury and the mechanisms. An intestinal mucositis model was established in C57/BL6 mice by 5-day administration of 5-FU (50 mg/kg every day, ip). MS-SOD (800 IU/10 g, ig) was given once daily for 9 days. 5-FU caused severe mucositis with intestinal morphological damage, bodyweight loss and diarrhea; MS-SOD significantly decreased the severity. 5-FU markedly increased reactive oxygen species (ROS) and inflammatory cytokines in the intestine which were ameliorated by MS-SOD. Furthermore, MS-SOD modified intestinal microbes, particularly reduced Verrucomicrobia, compared with the 5-FU group. In Caco2 cells, MS-SOD (250–1000 U/mL) dose-dependently decreased tBHP-induced ROS generation. In RAW264.7 cells, MS-SOD (500 U/mL) had no effect on LPS-induced inflammatory cytokines, but inhibited iNOS expression. These results demonstrate that MS-SOD can scavenge ROS at the initial stage of injury, thus play an indirect role in anti-inflammatory and barrier protein protection. In conclusion, MS-SOD attenuates 5-FU-induced intestinal mucositis by suppressing oxidative stress and inflammation, and influencing microbes. MS-SOD may exert beneficial effect in prevention of intestinal mucositis during chemotherapy in clinic.